Comparative study on direct and indirect methods for wet desulphurisation and denitrification based on micro-nano bubbles - Chen, Qin (Environmental technology, 2024)
The wet desulphurisation and denitrification technique based on micro-nano bubbles, which is available by either D-method or I-method, is a promising novel process. By employing piped water, Na2SO3 aqueous solution and HA-Na aqueous solution as the absorption liquids, a comparative study was conducted in this article on D-method and I-method to analyze their performance, advantages and disadvantages. It was accompanied by an investigation of how initial pH and initial temperature values of the absorption liquids affected the removal efficiency. The results suggested a positive correlation between NO/SO2 removal efficiencies and pH values but a little improvement in the removal efficiency under alkaline conditions. Furthermore, heating the absorption liquids inhibited the removal of NO and SO2. When manipulated in the same experimental environment, D-method and I-method did not present a significant difference in the SO2 removal efficiency, while the former was remarkably more effective than the latter in removing NO. To put together, D-method had higher removal efficiency, but required a large-scale micro-nano bubble generator to process a large quantity of flue gas as the micro-nano bubble generator was subject to a limited inlet flow rate. Consequently, an increase in investment and operating costs was incurred, while this issue could be avoided by I-method